Hidravlična ustreznost merilnih mest za merjenje pretokov - Cerar, Uroš (Acta hydrotechnica, 2000)
This paper presents the significance of flow measuring and a description of the methodology for the hydraulic verification of flow measuring sites. Flow measurements may be necessary within the technological process where the flow data, measured with defined accuracy, are vital for the control of the process. It can be also requested by an administrative act, for example, emission monitoring regulation. Specific knowledge, devices, experience and, at times, special procedures, are needed for the measurements. With years of experience, a procedure for hydraulic verification of flow measuring sites has been developed. Basically, it consists of three elements: velocity field measurements with flow calculation, verification of the measurement device regarding the international standards applied and verification of hydraulic boundary conditions with mathematical modeling. The application of this methodology on two case studies is presented
Keywords: hidrologija; kanalizacija; meritve; modeliranje; odpadne vode; pretok